The Development of Android Based on Legal Protection System for Women and Children - Hazilina, Hazilina; Alkadri, Syarifah Putri Agustini (UNISSULA, 2024)
The issue of protecting women and children is becoming a concern in many parts of the world, including Indonesia. Applications can help women and children face dangerous conditions, increase public awareness, and empower them in handling cases of sexual harassment, requiring alternative technology-based solutions. The research method is juridical-empirical using a positivism paradigm, with a population of Pontianak city. Data was collected through literature study, documentation, and questionnaires. The legal protection for women and children in Pontianak City in terms of overcoming violence was found to be good, The community believed that the government was not adequately addressing incidences of abuse against women and children. Supporting factors suggest that the public can be helped by reporting acts of violence online.